Hi,
well i think you mean ;
lim (x^2 +2x)/x
x ->0
if you just fill ' 0 ' in to this you will see ,
lim ( 0^2 +2*0)/ 0 = 0/0 and undefined
x ->
so you must simplify this first ;
{ factor ' x ' }
lim x ( x+2) / x { Here ,ignore ' x ' } so we have ;
x-> 0
lim x+2 = 0 + 2 = 2
x -> 0
The result is;
lim (x^2 +2x) / x = +2
x ->0
Good Luck...
2006-10-03 21:08:41
·
answer #1
·
answered by sweetie 5
·
4⤊
0⤋
Assuming this is,
lim (x^2 +2x) / x
x->0
Just take the x out as it's common from the top.
i.e,
lim x(x+2) / x = lim (x+2) = 2
x->0 x->0
So long as the same term can be cancelled off without the association of a value, just go ahead and cancel it off.
Else use L'Hopital's rule where since the top and bottom are both 0 in the fraction, this ratio is the same as that of the derivatives.
i.e. the limit is the same as
lim (2x+2) / 1 = 2
x->0
Hope this helps!
2006-10-03 23:13:37
·
answer #2
·
answered by yasiru89 6
·
0⤊
0⤋
As stated, you have a false inequality.
Guessing that you meant x^2 instead of x>2,
lim x-->0 x^2+2X/X =2
(Since x never equals 0, the x's in the 2nd term can be canceled, leaving x^2 + 2)
2006-10-03 20:27:56
·
answer #3
·
answered by Helmut 7
·
0⤊
0⤋
Is this a typo and you really mean
a) lim x-->0 (x^2 + 2x/x)
Or
b) lim x-->0 (x^2 + 2x)/x
Solutions:
a) lim x-->0 (x^2 + 2x/x)
= lim x-->0 (x^2 + 2) (as 2x/x = 2)
= 0^2 + 2
=2
b) lim x-->0 (x^2 + 2x)/x
= lim x-->0 x(x + 2)/x [as x^2 + 2x = x(x+2)]
= lim x-->0 (x + 2) (as x/x = 1)
= 0 + 2
=2
2006-10-03 20:24:10
·
answer #4
·
answered by Wal C 6
·
0⤊
1⤋
lim x-->0 (x^2 + 2x)/x
= lim x-->0 x(x + 2)/x
[as x-->0 x not equal to 0]
= lim x-->0 (x + 2)
= 0 + 2
=2
2006-10-03 23:06:00
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
answer = a million this is L'well-being center's Rule backwards. L'well-being center's Rule in actuality states that in case you plug the decrease of x (x=0, subsequently) into the equation ([a million-cos^2x]/x^2) and get an indefinite quotient (0/0, ?/?, -?/?, ?/-?,-?/-?), then you particularly can take the spinoff of the numerator and denominator one after the different and plug on your decrease back to get the astonishing answer. (word: L'well-being center's Rule could could be utilized countless situations in case you nonetheless get indefinite quotients, yet it is irrelevant subsequently, in view which you're given the respond, a million) subsequently, L'well-being center's rule could be utilized to the 2nd equation ([a million-cos^2x]/x^2) to get the 1st equation (sinx/x). in view which you're given lim x->0 sinx/x = a million, then you particularly comprehend that lim x->0 (a million-cos^2x)/x^2 = a million. *info* tutor that the 2nd equation will supply an indefinite quotient in case you plug in x=0: [a million-cos^2(0)]/0^2 (a million-a million^2)/0 0/0 (this is an indefinite quotient.) Take the spinoff of the numerator and denominator one after the different: ?(a million-cos^2x)/?x^2 (stick to chain rule) 2sinx/2x (simplify) sinx/x provided that lim x->0 sinx/x = a million, you may state that (a million-cos^2x)/x^2 = a million.
2016-10-18 11:15:18
·
answer #6
·
answered by wach 4
·
0⤊
0⤋
9
2006-10-03 20:13:41
·
answer #7
·
answered by Mohsen 1
·
0⤊
0⤋
I don't know... give up!!
2006-10-03 20:13:12
·
answer #8
·
answered by CK 3
·
0⤊
2⤋